Identification and characterization of fish oil supplements based on fatty acid analysis combined with a hierarchical clustering algorithm. Issue 7 (8th May 2014) - Khoomrung, Sakda; Raber, Georg; Laoteng, Kobkul; Francesconi, Kevin A.
<x xml:space="preserve">Abstract</x> We report a method for simple screening and quality assessment of fish oil supplements based on fatty acid profiles of 25 commercial fish oil supplements determined by using GC/MS with a hierarchical clustering algorithm. Different fatty acid profiles were obtained for the various fish oil products derived from different sources and processes. The contents of eicosapentaenoic acid (20:5 n‐3) and DHA (22:6 n‐3), and of other specific fatty acids as well, could be used as a chemotaxonomic marker to characterize the fish oils. A hierarchical clustering algorithm was then generated and used to efficiently categorize the fish oil products in terms of fish origin, oil components, and production process. <inline-graphic xlink:href="ark:/27927/pghntzxjjn" content-type="ejlt201300369-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> Identification of fish oil supplements.